Copyright vs. Patent: Exploring Intellectual Property Protection Boundaries for Software - Siswoyo, Amelia Anggriany; Sutiawan, Hendrik Agus; Rasjidi, Ira Thania (Universitas Islam Negeri Sumatera Utara, 2025)
This article examines the legal protection boundaries of software within the intellectual property system, particularly focusing on the ambiguity between copyright and patent regimes. The main issue addressed is whether software with technical functions should be protected solely through patents or whether copyright is sufficient, considering the dual nature of software as both an expressive work and a technological tool. Using a normative legal approach, this study analyzes the national legal framework and compares it with other jurisdictions. The research findings indicate that dual protection without clear boundaries may lead to legal uncertainty, especially for software industry players who require clarity regarding their exclusive rights. Therefore, a more assertive and harmonized legal policy formulation is needed to ensure optimal protection of software in both its creative and functional aspects.